Distribution and dynamics of antibiotic resistance genes in a three-dimensional multifunctional biofilm during greywater treatment. (15th June 2023) - Liu, Ying; Wu, Beibei; Cui, Xiaocai; Ren, Qingqing; Ren, Tian; Zhou, Yun
Abstract: Antibiotic resistance genes (ARGs) have been identified as serious threats to public health. Despite the widespread in various systems, dynamics of ARGs in three-dimensional multifunctional biofilm (3D-MFB) treating greywater are largely undefined. This work tracked the distributions and dynamics of eight target genes ( intI 1, korB, sul 1, sul 2, tetM, ermB, bla CTX-M and qnrS ) in a 3D-MFB during greywater treatment. Results showed that hydraulic retention times at 9.0 h achieved the highest linear alkylbenzene sulfonate (LAS) and total nitrogen removal rates at 99.4% and 79.6%, respectively. ARGs presented significant liquid-solid distribution feature, but non-significant with biofilm position. Intracellular ARGs (predominant by intI 1, korB, sul 1 and sul 2) at bottom biofilm were 210- to 4.2 × 10 4 - fold higher than that in cell-free liquid. Extracellular polymeric substances (EPS)-attached LAS showed linear relationship with most of ARGs ( R 2 > 0.90, P < 0.05). Sphingobacteriales, Chlamydiales, Microthrixaceae, SB-1, Cryomorphaceae, Chitinophagaceae, Leadbetterella and Niabella were tightly bound up with target ARGs. Key is that EPS-attached LAS considerably determines the occurrence of ARGs, and microbial taxa play an important role in the dissemination of ARGs in the 3D-MFB. Graphical abstract: Image 1 Highlights: Maximum biofilm thickness enabled highest removal rates of C and N in the system. Antibiotic resistance genes (ARGs) presented significant liquid-solid distribution feature. Extracellular polymeric substances-attached LAS considerably determines ARGs occurrence. Microbial taxa play an important role in the dissemination of ARGs. The membrane biofilm system constrained the discharge of ARGs in the effluent.